Visual Communication In English Short Stories Using Artificial Intelligence (AI) - M Reza Ishadi Fadillah; Devito Andharu; Rommel Utungga Pasopati; Kusuma Wijaya; Anggraeni Ramadhani; Anindya Thalita Salsabila (Gudang Jurnal Multidisiplin Ilmu, 2024)
The use of Artificial Intelligence (AI) technology to visualize the narrative of English-language short stories offers a novel approach to enriching the interpretive and aesthetic dimensions of storytelling. Utilizing BingImage.com as an AI-based image generator, textual narratives are transformed into prompts that create visual depictions of each scene. The visuals effectively reflect the mood, emotions, and settings of the story, albeit with some inconsistencies in character depictions across scenes. This exploratory approach examines correlations between narrative and visuals, scene continuity, and aesthetic accuracy. The findings indicate that AI-based visualization can create a more immersive reading experience, enhancing the reader's comprehension through relevant illustrations. This technology also provides creative interpretations that expand the artistic dimensions of short stories. Despite its potential, challenges such as maintaining visual consistency across scenes remain. These findings provide new insights into the integration of digital technology in literary transformation, paving the way for innovative future methodologies.